On stability analysis of a class of three-dimensional system of exponential difference equations - Abdul Khaliq; Haza Saleh Alayachi; Muhammad Zubair; Muhammad Rohail; Abdul Qadeer Khan (AIMS Mathematics, 2023)
The boundedness character, persistent nature, and asymptotic conduct of non-negative outcomes of the system of three dimensional exponential form of difference equations were studied in this research: